The integration of Quran memorization in university life: Analyze the challenges and impacts on academic performance - Luthfannia, Shefita Azkabella (Maliki Interdisciplinary Journal, 2024)
This article examines the phenomenon of integrating the Tahfidz Al-Quran program into college life, with a focus on the challenges faced by students and its impact on academic achievement. The study employs a conceptual approach to analyze the dynamics between Quran memorization activities and academic demands at university. The findings indicate that Quran-memorizing students encounter various challenges, such as time management, environmental adaptation, and balancing academic commitments with memorization responsibilities. However, empirical data from UIN Malang suggests that these students tend to achieve high academic performance, with an impressive average Grade Point Average (GPA). The research also reveals that the success of this integration is supported by factors like discipline, effective time management, and institutional support through specialized programs. This study offers valuable insights into aligning spiritual and academic education at the university level and recommends strategies to optimize both aspects.